1999
DOI: 10.1038/sj.mp.4000568
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Borna disease virus RNA from peripheral blood cells in schizophrenic patients and mental health workers

Abstract: Accumulating evidence suggests that Borna disease virus (BDV), a neurotropic, negativestranded RNA virus, might be associated with certain human mental disorders. Several research groups reported that psychiatric patients had a significantly higher prevalence of BDV serum antibodies than normal controls. In addition, a significantly higher presence of BDV RNA from peripheral blood cells was identified in mental patients than in controls. In our previous study, we first identified the presence of BDV serum anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 19 publications
0
20
1
Order By: Relevance
“…These four patients are strongly considered to be infected with BDV, although a significant association between BDV infection and human psychiatric disorders was not confirmed, unlike in previous studies (5,8,9,15,23,33,40,48,49,53). Further studies including a larger number of subjects may be necessary.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…These four patients are strongly considered to be infected with BDV, although a significant association between BDV infection and human psychiatric disorders was not confirmed, unlike in previous studies (5,8,9,15,23,33,40,48,49,53). Further studies including a larger number of subjects may be necessary.…”
Section: Discussioncontrasting
confidence: 45%
“…BDV is a noncytolytic neurotropic virus that infects a wide variety of animal species from birds to primates (7,17,26,36,51,52) and causes Borna disease (BD), which is characterized by central nervous system dysfunction with variable manifestations ranging from fatal neuronal damage to almost asymptomatic viral persistence (19,25,28,29). The wide host range of the virus and behavioral disturbances in animals with BD have suggested that BDV infection may be associated with human psychiatric disorders (5,8,9,15,23,33,40,48,49,53). Furthermore, seroepidemiological data and the detection of BDV RNA in peripheral blood mononuclear cells (PBMCs) by nested reverse transcriptase PCR (RT-PCR) have also suggested a possible involvement of BDV in human psychiatric disorders.…”
mentioning
confidence: 99%
“…In the mid-1990s, BDV core proteins N and P (3) and nucleic acid (4) were detected in PBMCs, leading to worldwide prevalence studies in patients (13,33). However, controversy ensued because of the heterogeneous results with respect to the lack of correlation between antibodies and RNA-positive cells, the low and discontinuous antibody titers in patients, and, at least in some studies, a similarly low antibody prevalence in controls and patients (9,32,38,43).…”
Section: Laboratory Parameters and Their Diagnostic Relevancementioning
confidence: 99%
“…Blood donors are tested for human immunodeficiency virus, hepatitis B virus, and hepatitis C virus infections, but from a gender and socioeconomic standpoint, the control group is far from being representative of the "normal" population. Based on reports of an elevated infection rate with BDV among healthy relatives of patients (13,32), a potentially higher risk of acquiring BDV infection should be envisioned in the healthy volunteers if a member of the family or a group tests positive for BDV (13,32,38).…”
Section: Prevalence Of Bdv Infection In Psychiatric Patients and Healmentioning
confidence: 99%
“…In few studies, BDV has been suggested as a contributing source for neuropsychiatric illness (Chen et al, 1999), but BDV and or its viral component has been reported to present in blood of psychiatric patients Bode et al, 1996;Heinrich and Adamaszek, 2010;Kitani et al, 1996;Sauder et al, 1996). In animal models, the transfusion/transfer of lymphocytes from brain of BDV-infected to immuno-compromised rats results in clinical symptoms and neuropathology of Borna disease in the recipients (Batra et al, 2003).…”
Section: Blood Transfusion and Bdvmentioning
confidence: 99%